2017
DOI: 10.1039/c7ra10289e
|View full text |Cite
|
Sign up to set email alerts
|

Efficient synthesis of butyl levulinate from furfuryl alcohol over ordered mesoporous Ti-KIT-6 catalysts for green chemistry applications

Abstract: Here we describe the synthesis of butyl levulinate by alcoholysis of furfuryl alcohol with n-butanol over a series of titanium incorporated mesoporous KIT-6 molecular sieve catalysts prepared by a simple sol–gel treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…A previous study showed that the solubility of hydrogen is higher in GVL solvent [28]. Besides, the hydrogenation of BL in GVL solvent allows to work at higher temperature due to the high vapor pressure of the different chemicals [52].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study showed that the solubility of hydrogen is higher in GVL solvent [28]. Besides, the hydrogenation of BL in GVL solvent allows to work at higher temperature due to the high vapor pressure of the different chemicals [52].…”
Section: Introductionmentioning
confidence: 99%
“…Methyl, ethyl and n-butyl levulinates are the three most studied AL. A thermal risk assessment of AL hydrogenation [36] showed that the risk of thermal runaway for the hydrogenation of methyl levulinate is higher than for butyl levulinate (BL), and the use of butanol for the alcoholysis of carbohydrates into BL is a promising route [52].…”
Section: Introductionmentioning
confidence: 99%
“…To get away from these issues, heterogeneous catalysts have been taken into account 8–10 . The number of heterogeneous acid catalysts such as Fe 2 (SO 4 ) 3 , 11 Ti‐KIT‐6, 12 Zr‐Al/SBA‐15, 13,14 zeolites, 15 ion exchange resin, 16 sulfonated carbon nanotubes, 17 sulfonic mesostructured silicas, 18 supported montmorillonite 19 has also been reported for the synthesis of levulinic acid esters such as BL prepared from biomass derivatives in n ‐BuOH as the solvent. However, most of these catalysts have some complications such as low activity and separation issues of solid acid catalyst from the reaction mixture, high cost, the extensive consumption of catalyst in the reaction, and complicated preparations and recycling process.…”
Section: Introductionmentioning
confidence: 99%
“…Low cost of furfuryl alcohol (FAL) as compared to levulinic acid, makes direct one-pot BL synthesis from FAL lot more attractive [10]. Several homogenous and heterogenous catalyst have been reported for synthesis of BL from FAL, however a number of recyclability and environmental issues have attracted the replacement of homogeneous catalyst with heterogeneous solid acid catalysts such as sulfonic acid functionalized ionic liquids [19], Al2O3/SBA-15 [5], Al-TUD-1 [20], double SO3H-functionalized ionic liquids [21], organo-inorganic hybrid catalyst [22], ion-exchange resin [23], zinc exchanged tungstophosphoric acid supported on niobium oxide [14] and zeolites [24]. Most of these catalysts are either expensive, hard to regenerate, less active, require high catalyst to substrate ratio, or need tedious method of preparation, making it unsuitable for commercialization.…”
Section: Introductionmentioning
confidence: 99%
“…To overcome such limitations and achieve higher dispersion, either they are immobilised on different supports and/or protons are partially or fully substituted with metal ions [23]. Different metal ions such as Cu, Cs, Pd, Ag, Al and Sn have been used to replace the H + ions in TPA [24,25]. Different supports such as silica, alumina, titania, tin oxide, niobia oxide and K-10 have been used to make solid acid catalysts for a range of organic transformations [23,26].…”
Section: Introductionmentioning
confidence: 99%